2012
DOI: 10.1016/j.dcn.2012.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Nonverbal spatially selective attention in 4- and 5-year-old children

Abstract: Under some conditions 4- and 5-year-old children can differentially process sounds from attended and unattended locations. In fact, the latency of spatially selective attention effects on auditory processing as measured with event-related potentials (ERPs) is quite similar in young children and adults. However, it is not clear if developmental differences in the polarity, distribution, and duration of attention effects are best attributed to acoustic characteristics, availability of non-spatial attention cues,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Future studies that include a broader variety of probe types, such as environmental sounds (i.e. Sanders and Zobel, 2012 ), different phonemes, or words as probes, could elucidate the parameters that affect the morphology of auditory ERPs and how they develop.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies that include a broader variety of probe types, such as environmental sounds (i.e. Sanders and Zobel, 2012 ), different phonemes, or words as probes, could elucidate the parameters that affect the morphology of auditory ERPs and how they develop.…”
Section: Discussionmentioning
confidence: 99%
“…Children had to selectively attend to the stimulus from one channel and inhibit their attention from the other. Studies with 5-yr old children showed a broad positivity across all electrode sites that peaked around 100ms after stimulus onset, rather than the positive-negative-positive (P1-N1 complex) ERP waveform characteristic of adults [ 65 , 67 , 69 ], which does not emerge until early adolescence [ 69 ]. While pre-schoolers did not have the ability to differentially attend to stories played in two channels [ 68 ], they could selectively attend to environmental sounds [ 67 ] as evidenced by the absence [ 68 ] and presence [ 67 ] of a negative oscillation in the ERP waveform respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This finding is unsurprising considering that research has consistently shown significant frontal activation during EF tasks in typically developing infants and children [ 100 102 ]. In three ERP studies on 3.5–5 year olds investigating selective attention using auditory tasks, a broad positivity has been observed 100ms post stimulus presentation as opposed to the distinct P1-N1 complex which is routinely seen in adults [ 65 , 67 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this area, Egeth [11] described the concept of the BCIs' application in locked-in children and adults based on previous research on auditory attention in children by Gomez et al [12] and Sanders et al [13]. Further studies in the area of auditory event-related potentials (ERPs) in 4-and 5-year-old children by Sanders et al [14] showed auditory processing quite similar in young children and adults. These findings may constitute promise towards further use of auditory ERPs in ERP-based BCIs in the youngest children with neurological disorders.…”
Section: Discussionmentioning
confidence: 99%